2017
DOI: 10.15171/apb.2017.018
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the hotspots involved in RON-MSPβ complex formation using in silico alanine scanning mutagenesis and molecular dynamics simulation

Abstract: Purpose: Implication of protein-protein interactions (PPIs) in development of many diseases such as cancer makes them attractive for therapeutic intervention and rational drug design. RON (Recepteur d’Origine Nantais) tyrosine kinase receptor has gained considerable attention as promising target in cancer therapy. The activation of RON via its ligand, macrophage stimulation protein (MSP) is the most common mechanism of activation for this receptor. The aim of the current study was to perform in silico alanine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…Translation of the obtained sequence showed that the mutation at position 19is silent while the two others have resulted in missense mutation at the positions 18 (S18G) and nonsense mutation of tryptophan at position 39to stop codon ( Figure 1). Previous studies have shown the variation of amino acid sequence of DOF 4.2-ZF MD simulations have been extensively used to virtually investigate proteinprotein/DNA and protein-small molecules interactions [27][28][29] . Different studies have used MD simulation based algorithms to report the interaction of DOF family proteins with DNA 26,30,31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Translation of the obtained sequence showed that the mutation at position 19is silent while the two others have resulted in missense mutation at the positions 18 (S18G) and nonsense mutation of tryptophan at position 39to stop codon ( Figure 1). Previous studies have shown the variation of amino acid sequence of DOF 4.2-ZF MD simulations have been extensively used to virtually investigate proteinprotein/DNA and protein-small molecules interactions [27][28][29] . Different studies have used MD simulation based algorithms to report the interaction of DOF family proteins with DNA 26,30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…MD simulations have been extensively used to virtually investigate protein-protein/DNA and protein-small molecules interactions. 27 - 29 Different studies have used MD simulation based algorithms to report the interaction of DOF family proteins with DNA. 26 , 30 , 31 Pandey et al explored the DNA binding ability of DOF domain from wheat showing that single K29R mutation could adversely affect its binding capability.…”
Section: Discussionmentioning
confidence: 99%
“…The above seven complexes were subsequently prepared for MD simulations with GROMACS v.5.0.6 (GROningen MAChine for Chemical Simulation) software package (Abraham et al, 2015). The AMBER99SB-ILDN forcefield was applied to generate the topology parameters of the structural complexes (Lindorff-Larsen et al, 2010;Venkatesan et al, 2015;Zarei, et al, 2017;Galeazzi et al, 2018). The binary complexes were then surrounded by dodecahedron periodic box of SPCE water molecules (Selent et al, 2013;Venkatesan et al, 2015;Galeazzi et al, 2018;Du et al, 2020).…”
Section: Analysis Of Interaction Dynamicsmentioning
confidence: 99%
“…In this paper, a novel method, namely, interaction entropy (IE) (Duan et al, 2016b), is used to calculate the entropy change, which is theoretically rigorous. It can yield more accurate results than the traditional Nmode method, which has been applied successfully to the calculation of the binding free energy in many studies (Duan et al, 2016a, 2017a,b; Aldeghi et al, 2017; Ben-Shalom et al, 2017; Cebrián-Prats et al, 2017; Chen et al, 2017a,b; Gao et al, 2017; Khammari et al, 2017; Nguyen Quoc et al, 2017; Sun et al, 2017; Wang et al, 2017; Yan et al, 2017; Yang et al, 2017; Zarei et al, 2017; Zou et al, 2017; Cong et al, 2018; Liu et al, 2018; Qiu et al, 2018; Song et al, 2018).…”
Section: Introductionmentioning
confidence: 99%